2018
DOI: 10.1002/ajhb.23144
|View full text |Cite
|
Sign up to set email alerts
|

The influence of biological affinity and sex on morphometric parameters of the clavicle in a South African sample

Abstract: Overall, the results of the present study indicate that the clavicle is an accurate predictor of sex and its dimensions are population-specific. Therefore, discriminant functions of the clavicle should only be used for sex estimation in forensic anthropology with the populations from which they were derived. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The diametric size of the human clavicle, for example, is closely measured and compared for Coloureds with Black Americans, White Americans, and Greeks. This research found that the clavicles of Coloured men are smaller than those of Black Americans (Scott et al 2018). Similarly, Coloured women have smaller clavicles than Coloured men.…”
Section: The Ideological Commitment To Finding Differencementioning
confidence: 65%
“…The diametric size of the human clavicle, for example, is closely measured and compared for Coloureds with Black Americans, White Americans, and Greeks. This research found that the clavicles of Coloured men are smaller than those of Black Americans (Scott et al 2018). Similarly, Coloured women have smaller clavicles than Coloured men.…”
Section: The Ideological Commitment To Finding Differencementioning
confidence: 65%